Soft contact lens with coating
The soft contact lens surface is solved by forming a first coating of hydrogel, a carboxyl and amino polymer polysaccharide and a second coating of glycidyl methacrylate on the surface of the soft contact lens, combined with covalent bonds, the soft contact lens surface is solved by forming a first coating of hydrogel, a first coating of carboxyl and aminopolymer polysaccharide and a second coating of glycidyl methacrylate on the surface of the soft contact lens, combined with covalent bonds, The problem of insufficient hydrophilicity and lubricity achieves the comfort and simplicity of manufacturing for a long time.
Patent Information
- Application Number
- CN202380044347.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-02
- Filing Date
- 2023-05-31
- Publication Date
- 2025-01-10
AI Technical Summary
The existing soft contact lenses have insufficient hydrophilicity and lubricity on the surface after long-term wear, resulting in discomfort in wearing, and the manufacturing process is complicated and economically unfavorable, and the durability evaluation is insufficient.
Using a structure including a hydrogel having a glycidyl group, a first coating and a second coating, the first coating consisting of a polymer and a polysaccharide derived from a carboxyl group and/or amino group, and the second coating derived from Monomers such as glycidyl methacrylate, 2-(meth)acryloyloxyethylphosphocholine, etc., are formed by covalent bonding to form a bilayer structure.
Even after a prolonged period of wearing, the surface of the soft contact lens remains sufficiently hydrophilic and lubricating, improving wear comfort, simplifying the manufacturing process and enhancing the durability of the coating.
Smart Images

Figure BDA0005164263270000261 
Figure BDA0005164263270000271 
Figure BDA0005164263270000272
Abstract
Description
Technical Field
[0001] The present invention relates to a soft contact lens including a coating layer having excellent surface hydrophilicity and lubricity and a method for manufacturing the lens. Background Art
[0002] It is reported that the number of wearers of soft contact lenses is increasing rapidly due to the ease of use and convenience of soft contact lenses, and the time of wearing soft contact lenses is increasing due to the ease of use and convenience, especially among young people (Non-Patent Document 1). The problems caused by the increase in the time of wearing soft contact lenses are insufficient oxygen to the wearer's cornea due to wearing soft contact lenses, and discomfort caused by wearing.
[0003] Since silicone hydrogel soft contact lenses allow sufficient oxygen to penetrate the cornea, adverse effects on corneal health can be minimized. However, due to its hydrophobicity, the wearer may experience dryness, discomfort, etc., and therefore hydrophilization of the contact lens surface is necessary.
[0004] As a method of hydrophilization, Patent Documents 1 and 2 disclose "a technology for imparting and enhancing hydrophilicity to the surface of a soft contact lens and improving wearing comfort by mixing polyethylene glycol, a cellulose polymer, etc. in a soft contact lens treatment solution".
[0005] Patent document 3 discloses "a technology for improving wearing comfort by adding a copolymer of a phosphorylcholine group-containing monomer and butyl methacrylate to a treatment liquid for soft contact lenses, the copolymer having a phospholipid-like structure derived from a biological membrane and known to have very high hydrophilicity and moisturizing effect".
[0006] Among these methods, although excellent hydrophilicity can be imparted to soft contact lenses, since adsorption is achieved on the surface of the contact lens only by physical interaction, there is a concern that the hydrophilicity may become insufficient when the contact lens is worn all day.
[0007] Patent Document 4 discloses “a technique for plasma processing soft contact lenses”.
[0008] Patent Document 5 discloses "a technique for hydrophilizing the surface of a soft contact lens by chemically bonding a soft contact lens having a reactive group and a hydrophilic polymer having a reactive group."
[0009] Among these methods, by treating the soft contact lens itself, it is possible to impart sufficient hydrophilicity to the surface of the soft contact lens even when the soft contact lens is worn all day.
[0010] Prior art documents
[0011] Non-patent literature
[0012] Non-patent literature 1: Walline JJ, 2013, Long-term Contact Lens Wear of Children and Teens, Eye & Contact Lens, Eyeglasses, 39, 283-289.
[0013] Patent Literature
[0014] Patent Document 1: WO2009 / 032122
[0015] Patent Document 2: WO2012 / 098653
[0016] Patent document 3: US2009 / 0100801
[0017] Patent Document 4: WO2010 / 092686
[0018] Patent Document 5: WO2001 / 074932 Summary of the invention
[0019] Problems to be solved by the present invention
[0020] In the method disclosed in Patent Document 4, since the surface treatment step is complicated, highly managed manufacturing equipment is required, which is also economically disadvantageous. In the method disclosed in Patent Document 5, the durability of the coating is not evaluated, and there is a concern that the hydrophilicity becomes insufficient when the soft contact lens is continuously worn for a long time.
[0021] An object of the present invention is to provide a soft contact lens in which two coating layers are formed on the surface and which has sufficient hydrophilicity and lubricity on the surface even when the soft contact lens is continuously worn for a long period of time.
[0022] Solutions to the problem
[0023] As a result of intensive studies, the present inventors have found that a soft contact lens including a hydrogel having a glycidyl group, a first coating layer having a carboxyl group and / or an amino group, and a second coating layer having a glycidyl group can solve the above problems, and have completed the present invention.
[0024] That is, the present invention is as follows.
[0025] 1. A soft contact lens comprising the following (1), (2) and (3):
[0026] (1) a hydrogel (P1) having a glycidyl group and comprising a glycidyl (meth)acrylate constituent unit;
[0027] (2) a first coating layer formed on the surface of the hydrogel and having carboxyl groups and / or amino groups, the first coating layer comprising a first polymer (P2) and / or a polysaccharide, the first polymer (P2) comprising a constituent unit derived from a carboxyl group-containing monomer and / or a constituent unit derived from an amino group-containing monomer, and the polysaccharide having carboxyl groups and / or amino groups; and
[0028] (3) A second coating layer formed on the surface of the first coating layer and having a glycidyl group, the second coating layer comprising a second polymer (P3), the second polymer (P3) comprising a constituent unit derived from glycidyl (meth)acrylate and a constituent unit derived from 2-(meth)acryloyloxyethyl phosphorylcholine, polyethylene glycol (meth)acrylate and / or methoxypolyethylene glycol methacrylate, wherein:
[0029] The glycidyl groups of the hydrogel are bonded to the carboxyl groups and / or amino groups of the first coating layer via covalent bonds, and the carboxyl groups and / or amino groups of the first coating layer are bonded to the glycidyl groups of the second coating layer via covalent bonds.
[0030] 2. The soft contact lens according to 1, wherein:
[0031] The first coating layer comprises a first polymer (P2) comprising a constituent unit derived from (meth)acrylic acid and / or a constituent unit derived from 2-aminoethyl (meth)acrylate.
[0032] 3. The soft contact lens according to item 1, wherein:
[0033] The second coating layer includes a second polymer (P3) comprising a constituent unit derived from 2-methacryloyloxyethyl phosphorylcholine.
[0034] 4. A method for manufacturing a soft contact lens according to any one of 1 to 3, the method comprising the following steps:
[0035] (1) immersing the hydrogel (P1) in a solution in which the first polymer (P2) and / or a polysaccharide having carboxyl groups and / or amino groups are dissolved; and
[0036] (2) A step of immersing the hydrogel having the first coating layer formed thereon after the step (1) in a solution in which the second polymer (P3) is dissolved.
[0037] Effects of the Invention
[0038] The soft contact lens according to the present invention has sufficient hydrophilicity and lubricity on the surface even in the case where the soft contact lens is worn continuously for a long period of time. DETAILED DESCRIPTION
[0039] (Soft contact lens and method for manufacturing the same)
[0040] The present invention relates to a soft contact lens comprising the following (1), (2) and (3) and a method for manufacturing the lens.
[0041] (1) A hydrogel (P1) having a glycidyl group and comprising a glycidyl (meth)acrylate constituent unit;
[0042] (2) a first coating layer formed on the surface of the hydrogel and having carboxyl groups and / or amino groups, the first coating layer comprising a first polymer (P2) and / or a polysaccharide, the first polymer (P2) comprising a constituent unit derived from a carboxyl group-containing monomer and / or a constituent unit derived from an amino group-containing monomer, and the polysaccharide having carboxyl groups and / or amino groups; and
[0043] (3) a second coating layer formed on the surface of the first coating layer and having a glycidyl group, the second coating layer comprising a second polymer (P3), the second polymer (P3) comprising a constituent unit derived from glycidyl (meth)acrylate, and a constituent unit derived from 2-(meth)acryloyloxyethyl phosphorylcholine, polyethylene glycol (meth)acrylate and / or methoxypolyethylene glycol methacrylate,
[0044] In the soft contact lens, the glycidyl groups of the hydrogel are bonded to the carboxyl and / or amino groups of the first coating via covalent bonds, and the carboxyl and / or amino groups of the first coating are bonded to the glycidyl groups of the second coating via covalent bonds.
[0045] In this specification, when describing a preferred numerical range (e.g., concentration range) in stages, each lower limit and upper limit can be independently combined. For example, in the description of "preferably 10 or more, more preferably 20 or more, and preferably 100 or less, more preferably 90 or less", "preferable lower limit: 10" and "more preferably upper limit: 90" can be combined as "10 or more and 90 or less". In addition, for example, the description of "preferably 10 to 100, more preferably 20 to 90" can also be combined as "10 to 90" in the same way.
[0046] In the present specification, "(meth)acrylate" means "acrylate or methacrylate", and the same applies to other similar terms.
[0047] <About Hydrogel>
[0048] The hydrogel of the present invention is obtained by preparing a monomer composition for hydrogel in which glycidyl (meth)acrylate is mixed with one or more other monomers, polymerizing the monomer composition, and further hydrating the obtained polymer for hydrogel.
[0049] The hydrogel of the present invention comprises constitutional units derived from individual monomers, the constitutional units being based on individual monomers or derived from individual monomers.
[0050] Examples of other monomers include hydrophilic monomers, hydrophobic monomers, silicone-containing monomers, crosslinking agents, and UV absorbing vinyl monomers.
[0051] The content of glycidyl (meth)acrylate is, for example, generally 0.1 to 20% by mass, and preferably 0.5 to 10% by mass, relative to 100% by mass of the monomer composition constituting the hydrogel.
[0052] Examples of hydrophilic monomers include: hydroxyl-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and glycerol (meth)acrylate; ionic group-containing monomers such as styrenesulfonic acid, (meth)acryloyloxyphosphonic acid, and 2-hydroxy-3-(meth)acryloxypropyltrimethylammonium chloride; nitrogen-containing monomers such as (meth)acrylamide, aminoethyl (meth)acrylate, N,N-dimethyl(meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylamide, N-acryloylmorpholine, 2-methacryloyloxyethylphosphocholine, N-vinylpyrrolidone, N-vinylacetamide, and N-methyl-N-vinylacetamide; polyethylene glycol (meth)acrylate; and glycidyl (meth)acrylate.
[0053] As the hydrophilic monomer, one or more of the above can be used. The content of the hydrophilic monomer is usually 10 to 99.9 mass %, preferably 20 to 99 mass %, and more preferably 30 to 98 mass %, relative to 100 mass % of the monomer composition constituting the hydrogel.
[0054] Examples of hydrophobic monomers include linear or branched alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate; cycloalkyl (meth)acrylates such as cyclohexyl (meth)acrylate; aromatic (meth)acrylates such as benzyl (meth)acrylate and phenoxyethyl (meth)acrylate; hydrophobic polyalkylene (meth)acrylates such as polypropylene glycol (meth)acrylate; and styrene monomers such as styrene, methylstyrene, and chloromethylstyrene.
[0055] As the hydrophobic monomer, one or two or more of the above can be used. The content of the hydrophobic monomer is usually 1 to 20% by mass, and preferably 5 to 10% by mass, relative to 100% by mass of the monomer composition constituting the hydrogel.
[0056] Examples of silicone-containing monomers include tris(trimethylsiloxy)silylpropyl methacrylate, 2-hydroxy-3-[3-[methylbis(trimethylsiloxy)silyl]propoxy]propyl methacrylate, 2-(methacryloyloxy)ethyl=3-[tris(trimethylsiloxy)silyl]propyl=succinate, polydimethylsiloxane (meth)acrylate, and methylbis(trimethylsiloxy)silylpropylglycerol methacrylate.
[0057] As the silicone-containing monomer, one or more of the above can be used. The content of the silicone-containing monomer is usually 5 to 90 mass %, preferably 15 to 80 mass %, and more preferably 30 to 70 mass %, relative to 100 mass % of the monomer composition constituting the hydrogel.
[0058] Examples of the crosslinking agent (monomer) include tetraethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, ethylene glycol di(meth)acrylate, tetraethylene glycol divinyl ether, triethylene glycol divinyl ether, diethylene glycol divinyl ether, ethylene glycol divinyl ether, trimethylolpropane trimethacrylate, pentaerythritol tetramethacrylate, bisphenol A dimethacrylate, vinyl methacrylate, ethylenediamine di(meth)acrylamide, glycerol dimethacrylate, triallyl isocyanurate, triallyl cyanurate, allyl (meth)acrylate, N-allyl (meth)acrylamide, 1,3-bis(methacrylamidopropyl)-1,1,3,3-tetrakis(trimethylsiloxy)disiloxane, N,N′-methylenebis(meth)acrylamide, N,N′-ethylenebis(meth)acrylamide and N,N′-dihydroxyethylenebis(meth)acrylamide.
[0059] As the crosslinking agent, one or two or more of these examples may be used, and tetraethylene glycol di(meth)acrylate, ethylene glycol di(meth)acrylate, glycerol dimethacrylate, or triethylene glycol divinyl ether is preferred.
[0060] The content of the crosslinking agent is usually 0.01% by mass to 10% by mass, preferably 0.1% by mass to 10% by mass, and more preferably 0.2% by mass to 5% by mass, relative to 100% by mass of the monomer composition constituting the hydrogel.
[0061] As monomers other than the above monomers, UV absorbing vinyl monomers may be mixed into the monomer composition for hydrogel. Examples of UV absorbing vinyl monomers include 2-(2-hydroxy-5-vinylphenyl)-2H-benzotriazole, 2-(2-hydroxy-5-acryloyloxy)phenyl)-2H-benzotriazole, 2-(2-hydroxy-3-methacrylamidemethyl-5-tert-octylphenyl)benzotriazole, 2-(2'-hydroxy-5'-methacrylamidephenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-5'-methacrylamidephenyl)-5-methoxybenzotriazole, 2-(2'-hydroxy-5'-methylacrylamidephenyl)-5-methoxybenzotriazole, 2-(2'-hydroxy-5'-methacryloxypropylphenyl)benzotriazole, 2-hydroxy-5-methoxy-3-(5-(trifluoromethyl)-2H-benzo[d][1,2,3]triazol-2-yl)benzyl methacrylate, 2-hydroxy-5-methoxy-3-(5-methoxy-2H-benzo[d][1,2,3]triazol-2-yl)benzyl methacrylate, 3-(5-fluoro-2H-benzo[d][ 1,2,3]triazol-2-yl)-2-hydroxy-5-methoxybenzyl methacrylate, 3-(2H-benzo[d][1,2,3]triazol-2-yl)-2-hydroxy-5-methoxybenzyl methacrylate, 3-(5-chloro-2H-benzo[d][1,2,3]triazol-2-yl]-2-hydroxy-5-methoxybenzyl methacrylate, 2-hydroxy-5-methoxy-3-(5-methyl-2H-benzo[d][1,2,3]triazol-2-yl)benzyl methacrylate, 2-Hydroxy-5-methyl-3-(5-(trifluoromethyl)-2H-benzo[d][1,2,3]triazol-2-yl)benzyl methacrylate, 4-allyl-2-(5-chloro-2H-benzo[d][1,2,3]triazol-2-yl)-6-methoxyphenol, 2-{2'-hydroxy-3'-tert-5'[3"-(4"-vinylbenzyloxy)propoxy]phenyl}-5-methoxy-2H-benzotriazole, phenol, 2-(5-chloro-2H-benzotriazol-2-yl)-6-(1,1-dimethylethyl)-4-vinyl, 2-(2'-hydroxy-5'-methacryloyloxyethylphenyl)benzotriazole (2-acrylic acid, 2-methyl-, 2-[3-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]ethyl ester, Norbloc), 2-{2'-hydroxy-3'-tert-butyl-5'-[3'-methacryloyloxypropoxy]phenyl}-5-methoxy-2H-benzotriazole, 2-[2'-hydroxy-3'-tert-butyl-5'-(3'-acryloyloxypropoxy)phenyl}-5-methoxy-2H-benzotriazole ]-5-trifluoromethyl-2H-benzotriazole, 2-(2'-hydroxy-5-methylacrylamidephenyl)-5-methoxybenzotriazole, 2-(3-allyl-2-hydroxy-5-methylphenyl)-2H-benzotriazole, 2-(2-hydroxy-3-methyl-5-methylphenyl)-2H-benzotriazole, 2-3'-tert-butyl-2'-hydroxy-5'-(3"-dimethylvinylsilylpropoxy)-2'-hydroxy-phenyl)-5-methoxybenzotriazole, 2-(2'-hydroxy-5'-methylacrylamidephenyl)-5-methoxybenzotriazole 2-(3-(tert-butyl)-5-(5-chlorobenzotriazol-2-yl)-4-hydroxyphenyl)-propyl methacrylate (CAS#96478-15-8) and 2-(3-(tert-butyl)-4-hydroxy-5-(5-methoxy-2H-benzo[d][1,2,3]triazol-2-yl)-propyl methacrylate (CAS#96478-15-8) )phenoxy)ethyl methacrylate; phenol, and 2-(5-chloro-2H-benzotriazol-2-yl)-6-methoxy-4-(2-propen-1-yl) (CAS#12601421-20-5); 2-[2-hydroxy-5-[3-(methacryloyloxy)propyl]-3-tert-butylphenyl]-5-chloro-2H-benzotriazole; phenol, 2-(5-vinyl-2H-benzotriazol-2-yl)-4-methyl-, homopolymer (9CI) (CAS#83063-87-0), etc. ,
[0062] The content of the UV absorbing vinyl monomer is usually 0.1 to 30 parts by mass, preferably 0.2 to 20 parts by mass, and more preferably 0.3 to 10 parts by mass, relative to 100 parts by mass of the monomer composition constituting the hydrogel.
[0063] The above-mentioned monomer composition for hydrogel may contain a solvent as needed. As the solvent, a solvent that does not react under polymerization conditions can be used, and examples thereof include: water, tetrahydrofuran, tripropylene glycol methyl ether, dipropylene glycol methyl ester, ethylene glycol n-butyl ether, acetone, methyl ethyl ketone, diethylene glycol n-butyl ether, diethylene glycol methyl ether, ethylene glycol phenyl ether, propylene glycol methyl ether, propylene glycol methyl ether acetate, dipropylene glycol methyl ether acetate, propylene glycol n-propyl ether, dipropylene glycol n-propyl ether, tripropylene glycol n-butyl ether, propylene glycol n-butyl ether, dipropylene glycol n-butyl ether, tripropylene glycol n-butyl ether, propylene glycol phenyl ether, dipropylene glycol dimethyl ether, polyethylene glycol, polypropylene glycol, ethyl acetate, butyl acetate, amyl acetate, lactic acid Methyl ester, ethyl lactate, isopropyl lactate, dichloromethane, chloroform, ethanol, 1-propanol, 2-propanol, 2-butanol, menthol, 1-hexanol, cyclohexanol, cyclopentanol, borneol, 2-pentanol, 3-pentanol, 2-hexanol, 3-hexanol, 3-methyl-2-butanol, 2-heptanol, 2-octanol, 2-nonanol, 2-decanol, 3-octanol, norborneol, tert-butyl alcohol, tert-pentanol, 2-methyl-2-pentanol, 2,3-dimethyl-2-butanol, 3-methyl-3-pentanol, 1-methylcyclohexanol, 2-methyl-2-hexanol, 3,7-dimethyl-3-octanol, 1-chloro-2-methyl-2-propanol, 2- methyl-2-heptanol, 2-methyl-2-octanol, 2-methyl-2-nonanol, 2-methyl-2-decanol, 3-methyl-3-hexanol, 3-methyl-3-heptanol, 4-methyl-4-heptanol, 3-methyl-3-octanol, 4-methyl-4-octanol, 3-methyl-3-nonanol, 4-methyl-4-nonanol, 3-methyl-3-octanol, 3-ethyl-3-hexanol, 3-methyl-3-heptanol, 4-ethyl-4-heptanol, 4-propyl-4-heptanol, 4-isopropyl-4-heptanol, 2,4-dimethyl-2-pentanol, 1-methylcyclopentanol, 1-ethylcyclopentanol, 1-ethylcyclopentanol, 3-Hydroxy-3-methyl-1-butene, 4-hydroxy-4-methyl-1-cyclopentanol, 2-phenyl-2-propanol, 2-methoxy-2-methyl-2-propanol, 2,3,4-trimethyl-3-pentanol, 3,7-dimethyl-3-octanol, 2-phenyl-2-butanol, 2-methyl-1-phenyl-2-propanol, 3-ethyl-3-pentanol, 1-ethoxy-2-propanol, 1-methyl-2-propanol, 1-methyl-2-pyrrolidone, N,N-dimethylpropionamide, dimethyl sulfoxide, dimethylformamide, dimethylacetamide and N-methylpyrrolidone, and one or more thereof can be used.
[0064] The polymerization of the monomer composition for hydrogel can be carried out by a conventionally known method. For example, the polymerization can be carried out using a known polymerization initiator such as a thermal polymerization initiator or a photopolymerization initiator.
[0065] Thermal polymerization initiators are known to those skilled in the art, and examples thereof include: azo-based polymerization initiators such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis[2-(2-imidazolin-2-yl)propane] disulfate dihydrate, 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] dihydrate, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] disulfate dihydrate, 2'-azobis(1-imino-1-pyrroloxazone-2-methylpropane) dihydrochloride, 2,2'-azobis[2-methyl-N-{1,1-bis(hydroxymethyl)-2-hydroxyethyl}propionamide], 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2'-azobis(2-methylpropionamidine) dihydrochloride, and 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide]; and peroxide polymerization initiators such as benzoyl peroxide, tert-butyl hydroperoxide, cumene hydroperoxide, lauroyl peroxide, tert-butyl peroxyhexanoate, and 3,5,5-trimethylhexanoyl peroxide, and one or more thereof can be used.
[0066] From the viewpoint of safety and availability, an azo-based polymerization initiator is preferred, and from the viewpoint of reactivity, 2,2′-azobisisobutyronitrile, 2,2′-azobis(2-methylpropionic acid)dimethyl ester, and 2,2′-azobis(2,4-dimethylvaleronitrile) are particularly preferred.
[0067] Examples of the photopolymerization initiator include acetophenone, benzophenone, 2-benzoylbenzoic acid, 4-benzoylbenzoic acid, methyl 2-benzoylbenzoate, benzoin methyl ether, benzoin ethyl ether, benzoin isobutyl ether, diethoxyacetophenone, 2-isopropoxybenzophenone, 2-ethylanthraquinone, 2,4-diethylthioxanthene-9-one, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, bis-(2,6-dichlorobenzoyl)-4-N-propylphenylphosphine oxide and bis-(2,6-dichlorobenzoyl)-4-N-butylphenylphosphine oxide, which are Darocur (registered trademark) type and Irgacur (registered trademark) type.
[0068] Preferred are Darocur (registered trademark) 1173, Darocur (registered trademark) 2959, and Irgacur (registered trademark) 819. For example, a reactive photoinitiator capable of incorporating a macromonomer or capable of serving as a special monomer is also preferred.
[0069] The polymer for hydrogel can be obtained by a method known to those skilled in the art, and is produced, for example, by using a mold (gold mold) having a hydrophobic surface made of polypropylene or the like, filling the mold with a monomer composition for hydrogel, and polymerizing the monomer composition.
[0070] The polymerization reaction can be carried out in air, and can be carried out in an inert gas atmosphere such as nitrogen or argon to increase the polymerization rate. In the case of polymerization in an inert gas atmosphere, the pressure in the polymerization system is preferably 1 kgf / cm 2 the following.
[0071] The hydrogel polymer obtained as described above can be peeled off from the mold by a known method and taken out in a dry state. In addition, the hydrogel polymer can be immersed in a solvent (e.g., water, methanol, ethanol, 1-propanol, 2-propanol, and a mixed solution thereof) together with the mold to swell the contact lens substrate and peel off.
[0072] In addition, by repeatedly immersing the hydrogel polymer in a solvent for washing, it is possible to remove residues, residues, by-products, etc. of each component. For example, the hydrogel polymer can be washed by immersing it in the above-mentioned alcohol or an aqueous alcohol solution having a concentration of 30% by mass or more at 10°C to 40°C.
[0073] After washing, the polymer for hydrogel may be further washed by immersing it in an aqueous alcohol solution having an alcohol concentration of 20% by mass to 50% by mass for 10 minutes to 5 hours.
[0074] The hydrogel of the present invention can be obtained by immersing the polymer for hydrogel in water for 10 minutes to 5 hours after alcohol washing.
[0075] Before washing with water, a washing step of immersing the polymer for hydrogel in an alcohol aqueous solution having an alcohol concentration of 20 to 50 mass % for 10 minutes to 5 hours may be added. The water is preferably pure water such as RO water, ion exchange water, and distilled water.
[0076] <About the first coating>
[0077] The first polymer (P2) constituting (contained in) the first coating layer is not particularly limited, as long as the first polymer (P2) includes a first polymer (P2) containing constituent units derived from carboxyl-containing monomers and / or constituent units derived from amino-containing monomers and / or a polysaccharide having carboxyl groups and / or amino groups.
[0078] The constitutional unit refers to a unit based on each monomer or a compound contained in a polymer derived from each monomer.
[0079] Examples of carboxyl group-containing monomers (carboxyl group-containing compounds) include N,N-2-acrylamidoglycolic acid, β-methyl-acrylic acid (crotonic acid), β-acryloyloxypropionic acid, sorbic acid, angelic acid, cinnamic acid, 1-carboxy-4-phenyl-1,3-butadiene, itaconic acid, citraconic acid, mesoaconitic acid, glutaric acid, aconitic acid, maleic acid, fumaric acid, (meth)acrylic acid, 2-(meth)acryloyloxyethylsuccinic acid, 2-(meth)acryloyloxyethylhexahydrophthalic acid, 2-(meth)acryloyloxyethyl-phthalic acid and vinylbenzoic acid.
[0080] In addition, the polymer having a carboxyl group includes as a main component poly(meth)acrylic acid, alginic acid, xanthan gum, gellan gum, gum arabic, pectin, carrageenan, gum karaya, succinoglycan, hyaluronic acid, chondroitin sulfate, polyethylene glycol (PEG) having one carboxyl group at the terminal (e.g., HO-PEG-COH, H3CO-PEG-COOH), PEG having carboxyl groups at both terminals (HOOC-PEG-COH), multi-arm PEG having more than one carboxyl group, PEG amine dendrimers, etc. (Meth)acrylic acid is preferred, and methacrylic acid is more preferred.
[0081] Examples of the amino group-containing monomer (amino group-containing compound) include aminoethyl methacrylate (2-aminoethyl methacrylate), dimethylaminoethyl (meth)acrylate, and N,N-dimethylaminopropyl (meth)acrylamide. Aminoethyl methacrylate (2-aminoethyl methacrylate) is preferred.
[0082] The first polymer (P2) may be a copolymer with other monomers other than the above-mentioned compounds, and examples of the other monomers include: (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, stearyl (meth)acrylate, perfluoroalkylethyl (meth)acrylate, phenyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-aminoethyl (meth)acrylate and its salts, methoxypolyethylene glycol (meth)acrylate, and (meth)acrylates and Monoesters of polyethylene glycol; unsaturated nitriles such as (meth) acrylonitrile; unsaturated amides such as (meth) acrylamide, N-hydroxymethyl (meth) acrylamide and N-(2-hydroxyethyl) (meth) acrylamide; vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether and ethyl vinyl ether; α-olefins such as ethylene and propylene; halogen-containing α, β-unsaturated monomers such as vinyl chloride, vinylidene chloride and vinyl fluoride; and α, β-unsaturated aromatic monomers such as styrene, α-methylstyrene and sodium styrene sulfonate. Butyl (meth) acrylate is preferred, and butyl methacrylate is more preferred.
[0083] The amount of constituent units derived from carboxyl-containing monomers and / or constituent units derived from amino-containing monomers contained in the above-mentioned first polymer (P2) is preferably 10 mol % to 95 mol %, more preferably 20 mol % to 90 mol %, and further preferably 25 mol % to 80 mol %, relative to 100 mol % of all constituent units.
[0084] The weight average molecular weight of the above-mentioned first polymer (P2) is preferably 5,000 to 1,000,000, and more preferably 100,000 to 800,000.
[0085] As the first polymer (P2), a commercially available polymer can be used.
[0086] Examples of the polysaccharide having a carboxyl group and / or an amino group include alginic acid, xanthan gum, gellan gum, gum arabic, pectin, carrageenan, karaya gum, succinoglycan, hyaluronic acid, and chondroitin sulfate.
[0087] <About the Second Coating>
[0088] The second polymer (P3) constituting (contained in) the second coating layer is not particularly limited as long as the second polymer (P3) contains constituent units derived from glycidyl (meth)acrylate and constituent units derived from 2-(meth)acryloyloxyethyl phosphorylcholine, polyethylene glycol (meth)acrylate and / or methoxypolyethylene glycol methacrylate.
[0089] The constitutional unit refers to a unit based on each monomer or a compound contained in a polymer derived from each monomer.
[0090] The second polymer (P3) can be a copolymer with other monomers other than glycidyl (meth)acrylate, 2-(meth)acryloyloxyethyl phosphorylcholine, polyethylene glycol (meth)acrylate and / or methoxypolyethylene glycol methacrylate compounds, and examples of the other monomers include: hydroxyl-containing (meth)acrylates, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate and glycerol (meth)acrylate; ionic group-containing monomers, such as styrenesulfonic acid, (meth)acryloyloxyphosphonic acid and 2-hydroxy-3-(meth)acryloyloxypropyltrimethylammonium chloride; and nitrogen-containing monomers, such as (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N-acryloylmorpholine, N-vinylpyrrolidone, N-vinylacetamide and N-methyl-N-vinylacetamide.
[0091] As the hydrophilic monomer other than the monomer having a glycidyl group, one or more of these monomers can be used, preferably 2-methacryloyloxyethyl phosphorylcholine, N-vinyl pyrrolidone and polyethylene glycol (meth)acrylate, and more preferably -methacryloyloxyethyl phosphorylcholine (MPC).
[0092] The amount of the constituent unit derived from glycidyl (meth)acrylate contained in the second polymer is preferably 5 to 95 mol %, more preferably 7 to 90 mol %, and further preferably 10 to 80 mol % relative to 100 mol % of all constituent units.
[0093] The weight average molecular weight of the above-mentioned second polymer is preferably 5,000 to 1,000,000, and more preferably 100,000 to 800,000.
[0094] <Polymerization Reaction>
[0095] The polymerization reaction for obtaining the above-mentioned first polymer (first coating) and the second polymer (second coating) can be carried out by known methods, such as by replacing with an inert gas such as nitrogen, carbon dioxide, argon or helium or in the atmosphere of the inert gas, in the presence of a free radical polymerization initiator, free radical polymerization is carried out, for example, bulk polymerization, suspension polymerization, emulsion polymerization and solution polymerization. From the perspective of purification, solution polymerization is preferred. The purification of polymer can be carried out by general purification methods, such as reprecipitation, dialysis or ultrafiltration.
[0096] Examples of the radical polymerization initiator include azo-based radical polymerization initiators, organic peroxides, and persulfates.
[0097] Examples of the azo-based radical polymerization initiator include 2,2′-azobis(2-methylpropionamidine) dihydrochloride, 2,2-azobis(-2-diaminopropyl) dichloride, 2,2-azobis(2-(5-methyl-2-imidazolin-2-yl)propane) dihydrochloride, 4,4-azobis(4-cyanovaleric acid), 2,2-azobisisobutyramide dihydrate, 2,2-azobis(2,4-dimethylvaleronitrile) and 2,2-azobisisobutyronitrile (AIBN).
[0098] Examples of the organic peroxide include tert-butyl peroxyneodecanoate (Perbutyl (registered trademark) ND), benzoyl peroxide, diisopropyl peroxydicarbonate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxypivalate, tert-butyl peroxydiisobutyrate, lauroyl peroxide, and succinic acid peroxide (=succinyl peroxide).
[0099] Examples of persulfates include ammonium persulfate, potassium persulfate, and sodium persulfate.
[0100] These radical polymerization initiators may be used alone or in combination of two or more thereof. The amount of the polymerization initiator used is usually 0.001 to 10 parts by mass, and preferably 0.01 to 5.0 parts by mass, relative to 100 parts by mass of the monomer composition of the hydrophilic polymer.
[0101] The polymerization reaction can be carried out in the presence of a solvent, and as the solvent, a solvent that dissolves the monomer composition and does not participate in the reaction can be used. Examples of the solvent include: water; alcohol solvents such as methanol, ethanol, n-propanol, and isopropanol; ketone solvents such as acetone, methyl ethyl ketone, and diethyl ketone; ester solvents such as ethyl acetate; linear or cyclic ether solvents such as ethyl cellosolve, tetrahydrofuran, and N-methylpyrrolidone; and nitrogen-containing solvents such as acetonitrile and nitromethane. Preferred examples thereof include water or a mixed solvent thereof.
[0102] <Method for Manufacturing Soft Contact Lenses>
[0103] The method for producing the soft contact lens of the present invention is not particularly limited as long as the method includes the steps of bonding the hydrogel and the first polymer to each other via a covalent bond, and further bonding the first polymer and the second polymer to each other via a covalent bond. For example, the following steps can be exemplified.
[0104] (1) A step of immersing the hydrogel (P1) in a solution in which the first polymer (P2) and / or a polysaccharide having a carboxyl group and / or an amino group is dissolved.
[0105] (2) A step of immersing the hydrogel having the first coating layer formed thereon after the immersion in (1) in a solution in which the second polymer (P3) is dissolved.
[0106] <Reaction between hydrogel and first coating>
[0107] The hydrogel and the first coating layer (first polymer) are bonded to each other via a covalent bond by reacting the glycidyl group in the hydrogel with the carboxyl group and / or amino group in the first polymer.
[0108] The above reaction is performed by immersing the hydrogel in a solution in which the first polymer is dissolved at a temperature of about 20° C. to about 90° C. for about 0.2 hours to about 24 hours, preferably about 0.5 hours to about 12 hours, and further preferably about 1 hour to 6 hours.
[0109] The solvent in which the first polymer is dissolved is not particularly limited as long as it is a solvent that dissolves the first polymer and does not participate in the reaction, and is preferably water, methanol, ethanol, 1-propanol, 2-propanol, or a mixed solvent thereof.
[0110] The above reaction may be carried out together with the step of washing the polymer for the hydrogel. For example, the above reaction is carried out by immersing the hydrogel in a washing solution in which the first polymer is dissolved, and washing the hydrogel at a temperature of about 20° C. to about 90° C. for about 0.2 hours to about 24 hours, preferably about 0.5 hours to about 12 hours, and further preferably about 1 hour to 6 hours.
[0111] <Reaction between the first coating and the second coating>
[0112] In the reaction between the first coating layer and the second coating layer, the carboxyl group and / or the amino group in the first polymer and the glycidyl group in the second polymer are reacted with each other to be bonded via a covalent bond.
[0113] The above reaction is performed by immersing the hydrogel obtained by reacting the first polymer in a solution in which the second polymer is dissolved at a temperature of about 20° C. to about 125° C. for about 0.2 hour to about 24 hours, preferably about 0.5 hour to about 12 hours, and further preferably about 1 hour to 6 hours.
[0114] The solvent for dissolving the second polymer is not particularly limited as long as it is a solvent that dissolves the second polymer and does not participate in the reaction, and is preferably water, methanol, ethanol, 1-propanol, 2-propanol, or a mixed solvent thereof.
[0115] The above reaction may be carried out together with the step of washing the hydrogel after the reaction with the first polymer. For example, the above reaction is carried out by immersing the hydrogel after the reaction with the first polymer in a washing solution in which the second polymer is dissolved at a temperature of about 20° C. to about 90° C. and washing the hydrogel for about 0.2 hour to about 24 hours, preferably about 0.5 hour to about 12 hours, and further preferably about 1 hour to 6 hours.
[0116] The above reaction can be carried out together with the sterilization step of the hydrogel after reacting with the first polymer. For example, the hydrogel after reacting with the first polymer is immersed in a lens package or a sealed vial together with a physiological saline solution in which the second polymer is dissolved. Thereafter, the above reaction is carried out by autoclaving at a temperature of about 118° C. to about 125° C. for about 20 minutes to 90 minutes.
[0117] <Configuration Example of Soft Contact Lens of the Present Invention>
[0118] Examples of the configuration of the soft contact lens of the present invention include, but are not particularly limited to, the following combinations.
[0119] (1) The hydrogel comprises a constituent unit derived from glycidyl methacrylate, the first coating layer comprises a constituent unit derived from methacrylic acid, and the second coating layer comprises a constituent unit derived from glycidyl methacrylate and a constituent unit derived from 2-(meth)acryloyloxyethyl phosphorylcholine.
[0120] (2) The hydrogel comprises a constituent unit derived from glycidyl methacrylate, the first coating layer comprises a constituent unit derived from 2-aminoethyl methacrylate, and the second coating layer comprises a constituent unit derived from glycidyl methacrylate and a constituent unit derived from methoxypolyethylene glycol methacrylate.
[0121] (3) The hydrogel comprises a constituent unit derived from glycidyl methacrylate, the first coating layer comprises polyacrylic acid (preferably having a weight average molecular weight of 5,000 to 1,000,000), and the second coating layer comprises a constituent unit derived from glycidyl methacrylate and a constituent unit derived from 2-(meth)acryloyloxyethyl phosphorylcholine.
[0122] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples.
[0123] The components used in Synthesis Examples, Examples, and Comparative Examples are shown below.
[0124] GdMA: Glycidyl methacrylate
[0125] HEMA: 2-Hydroxyethyl Methacrylate
[0126] HBMA: 2-Hydroxybutyl Methacrylate
[0127] NVP: N-vinyl pyrrolidone
[0128] DMAA: N,N-dimethylacrylamide
[0129] MMA: Methyl Methacrylate
[0130] ETS: 2-(Methacryloxy)ethyl=3-[tris(trimethylsiloxy)silyl]propyl=succinate
[0131] SiGMA: Methylbis(trimethylsiloxy)silylpropylglycerol methacrylate
[0132] MCR-M11: Polydimethylsiloxane single-end methacrylate with a molecular weight of about 1000
[0133] TEGDMA: Tetraethylene glycol dimethacrylate
[0134] EtOH: ethanol
[0135] NPA: 1-propanol (n-propanol)
[0136] AIBN: 2,2'-azobis(isobutyronitrile)
[0137] I-819: Irgacur (registered trademark) 819 (phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide)
[0138] MAA: Methacrylic acid
[0139] PAA: Polyacrylic acid
[0140] AEMA: 2-aminoethyl methacrylate
[0141] MPC: 2-methacryloyloxyethyl phosphorylcholine
[0142] PME-1000: methoxy polyethylene glycol methacrylate with a molecular weight of about 1000
[0143] BMA: Butyl Methacrylate
[0144] PB-ND: tert-Butyl Peroxyneodecanoate
[0145] V-50: 2,2'-Azobis(2-methylpropionamidine) dihydrochloride
[0146] [Adjustment of hydrogel]
[0147] <Synthesis example 1-1>
[0148] 2.0 mass% of GdMA, 12.5 mass% of HBMA, 30.0 mass% of NVP, 5.0 mass% of MMA, 20.0 mass% of SiGMA, 30.0 mass% of MCR-M11, 0.50 mass% of TEGDMA, and 10.0 mass parts of NPA were mixed, and then 0.5 mass parts of AIBN was dissolved therein to obtain a composition for hydrogel.
[0149] The composition for hydrogel was dispensed into a mold and heated in a polymerization furnace set at 100° C. for 2 hours to obtain a polymer for hydrogel.
[0150] The polymer was taken out from the mold, immersed in about 20 g of a solution of 2-propanol:ion exchange water=1:1 for 4 hours, and then immersed in about 20 g of ion exchange water for 2 hours to obtain a hydrogel having a glycidyl group.
[0151] <Synthesis Examples 1-2 and 1-3>
[0152] Except that the mixing ratio of each component in the composition and the polymerization conditions were changed as shown in Table 1, a hydrogel having a glycidyl group was prepared in the same manner as in Synthesis Example 1-1.
[0153] In Synthesis Example 1-2, the hydrogel composition dispensed into the mold was placed in a UV-LED irradiator (irradiation light wavelength: 405 nm) and irradiated at room temperature at 1.5 mW / cm 2 The polymer was irradiated with UV light at an irradiation intensity of 1000 nm for 30 minutes to obtain a hydrogel.
[0154] [Adjustment of the first polymer solution (first coating solution)]
[0155] <Synthesis example 2-1>
[0156] A polymerization solution was obtained by dissolving 19.4 g of MAA and 3.6 g of BMA in 57.5 g of water and 57.5 g of EtOH. After the temperature of the polymerization solution was raised to 55° C. under a nitrogen atmosphere, 0.12 g of V-50 was added to initiate polymerization. After 3 hours, the temperature was raised to 75° C., and the mixture was further reacted for 2 hours to obtain a copolymer solution. After removing impurities from the obtained polymer solution by dialysis purification, the solution was diluted with water so that the concentration of the first polymer became 5% by mass, thereby obtaining a first polymer aqueous solution.
[0157] The method of measuring the weight average molecular weight of the obtained copolymer is as follows: In addition, the measurement was also performed in the same manner in Synthesis Examples 2-2 to 3-1 to 3-3.
[0158] 1 mg of the copolymer was dissolved in 1 g of purified water.
[0159] Column: SB-802.5HQ+SB-806MN HQ
[0160] Mobile phase: 20 mM phosphate buffer (pH: 7.0)
[0161] Standard material: Polyethylene glycol / oxide
[0162] Measuring instrument: HLC-8320GPC (manufactured by TOSOH CORPORATION)
[0163] Calculation method of weight average molecular weight: Molecular weight calculation program (EcoSEC Date Analysis)
[0164] Flow rate: 0.5 mL per minute
[0165] Injection volume: 100 μL
[0166] Column furnace: 45°C
[0167] Measurement time: 70 minutes
[0168] <Synthesis example 2-2>
[0169] A polymerization solution was obtained by dissolving 23.2 g of AEMA and 2.8 g of BMA in 65.0 g of water and 65.0 g of EtOH. After the temperature of the polymerization solution was raised to 55 ° C under a nitrogen atmosphere, 0.13 g of V-50 was added to initiate polymerization. After 3 hours, the temperature was raised to 75 ° C, and the mixture was further reacted for 2 hours to obtain a copolymer solution. After removing impurities from the obtained polymer solution by dialysis purification, the solution was diluted with water so that the concentration of the first polymer became 5% by mass, thereby obtaining a first polymer aqueous solution.
[0170] <Synthesis example 2-3>
[0171] A commercially available polymer may be used as the first polymer, and the first polymer may be diluted with water using commercially available PAA (average molecular weight: 250,000) so that the concentration of the first polymer is 5% by mass, thereby obtaining a first polymer solution.
[0172] [Preparation of the Second Polymer Solution (Second Coating Solution)]
[0173] <Synthesis example 3-1>
[0174] 2.8 g of GdMA and 23.6 g of MPC were dissolved in a mixed solvent of 52.8 g of water and 52.8 g of ethanol to obtain a polymerization solution. After the temperature of the polymerization solution was raised to 55 ° C under a nitrogen atmosphere, 0.17 g of PB-ND was added to initiate polymerization. After 3 hours, the temperature was raised to 75 ° C, and the mixture was further reacted for 2 hours to obtain a copolymer solution. After removing impurities from the obtained polymer solution by dialysis purification, the solution was diluted with water so that the concentration of the second polymer became 5% by mass, thereby obtaining a second polymer aqueous solution.
[0175] <Synthesis Examples 3-2 and 3-3>
[0176] Except that the amount of each component in the polymerization solution and the polymerization conditions were changed as shown in Table 2, a second polymer aqueous solution was obtained in the same manner as in Synthesis Example 3-1.
[0177] [evaluate]
[0178] <Transparency>
[0179] The clarity of the hydrogels (before coating) and contact lenses (after coating) was assessed visually.
[0180] <Water content>
[0181] The water content of hydrogels and contact lenses was measured according to the method described in ISO 18369-4.
[0182] <Elongation at break>
[0183] According to JIS-K7127, the elongation at break of the hydrogel and the contact lens was measured using a breaking strength analyzer, BAS-3305(W), manufactured by YAMADEN co.,ltd. A 2N load cell was used. As the measurement sample, a hydrogel or a contact lens cut to a width of 2 mm was used, pulled at a rate of 1 mm / s with a clamping interval of 6 mm, and the elongation at break was evaluated based on the position where the sample broke.
[0184] <Oxygen permeability coefficient (Dk)>
[0185] The oxygen permeability coefficient of the contact lens was measured according to the method described in ISO18369-4.
[0186] <WBUT: Water break-up time>
[0187] For the WBUT of the hydrogel and the contact lens, the hydrogel and the contact lens were gently taken out, and the time until the water film on its surface broke was measured with a stopwatch.
[0188] When the WBUT was 10 seconds or more, good wettability was determined.
[0189] <Lubricity>
[0190] For comparison, the lubricity of polymacon (a soft contact lens containing 2-hydroxyethyl methacrylate (HEMA) as a main component) and omafilcon A (a soft contact lens containing 2-hydroxyethyl methacrylate and 2-methacryloyloxyethyl phosphorylcholine as main components) at the fingertip was evaluated by sensory evaluation.
[0191] The evaluation was made on a 10-point scale, and when the surface lubricity of polymacon was 2 and that of omafilcon A was 8, the scores were as follows.
[0192] 1: The lowest lubricity.
[0193] 10: The highest lubricity.
[0194] When the score was 6 or more, good lubricity was determined.
[0195] <Durability>
[0196] The contact lens was rinsed with a physiological saline solution, then placed with the inner side of the lens facing up on the palm of the hand opposite to the dominant hand, and 1 mL of physiological saline solution was dropped thereon. The pad of the index finger of the dominant hand was brought into contact with the inner side of the contact lens and gently pressed, and the lens was moved forward, backward, left, and right and rubbed 30 times for cleaning. After repeating the operation 14 times and 30 times, the lubricity and wettability were evaluated respectively.
[0197] A: Wettability and lubricity are not reduced.
[0198] B: Wettability or lubricity is reduced.
[0199] C: Wettability and lubricity are reduced.
[0200] <Example 1>
[0201] The hydrogel prepared in Synthesis Example 1-1 was used as the hydrogel. The hydrogel was immersed in the first polymer solution prepared in Synthesis Example 2-1 and heated at 75° C. for 2 hours in the presence of a catalytic amount of triethylamine, thereby bonding the hydrogel and the first polymer to each other via a covalent bond and forming a first coating on the surface of the hydrogel.
[0202] Next, the hydrogel having the first coating was immersed in the second polymer solution prepared in Synthesis Example 3-1 and heated at 75° C. for 2 hours in the presence of a catalytic amount of triethylamine, so that the second polymer was bonded to the first polymer via a covalent bond to obtain a contact lens having a hydrophilic coating on the surface.
[0203] The obtained contact lenses were thoroughly washed with water, then immersed in a physiological saline solution adjusted according to ISO18369-3, and sterilized at 121°C for 20 minutes, and various evaluations were performed.
[0204] <Examples 2 and 4>
[0205] In the same manner as in Example 1 except that the hydrogel, the first polymer, and the second polymer were changed as shown in Table 3, a contact lens having a hydrophilic coating on the surface was obtained and various evaluations were performed.
[0206] <Example 3>
[0207] The hydrogel prepared in Synthesis Example 1-3 was used as the hydrogel. The hydrogel was immersed in the first polymer solution prepared in Synthesis Example 2-2 and heated at 90° C. for 2 hours, thereby bonding the hydrogel and the first polymer to each other via a covalent bond and forming a first coating on the surface of the hydrogel.
[0208] Next, the hydrogel having the first coating was immersed in a physiological saline solution containing 0.1 mass % of the second polymer prepared using the second polymer solution prepared in Synthesis Example 3-2, and sterilized at 121° C. for 20 minutes to bond the second polymer to the first polymer via a covalent bond, thereby obtaining a contact lens having a hydrophilic coating on the surface, and various evaluations were performed.
[0209] <Comparative Example 1>
[0210] Methafilcon A (contact lens made of a copolymer of HEMA and MAA) was used as the hydrogel. The hydrogel was immersed in the second polymer solution prepared in Synthesis Example 3-3 and heated at 75°C for 2 hours in the presence of a catalytic amount of triethylamine, thereby bonding the second polymer to the hydrogel via a covalent bond, and obtaining a contact lens having only the second polymer coated on the surface of the hydrogel.
[0211] The obtained contact lenses were thoroughly washed with water, then immersed in a physiological saline solution adjusted according to ISO18369-3, and sterilized under the conditions of 121° C. and 20 minutes, and various evaluations were performed.
[0212] <Comparative Example 2>
[0213] The hydrogel prepared in Synthesis Example 1-1 was used. The hydrogel was immersed in the first polymer solution prepared in Synthesis Example 2-1 and heated at 75° C. for 2 hours in the presence of a catalytic amount of triethylamine, thereby bonding the first polymer to the hydrogel via a covalent bond, and obtaining a contact lens having only the first polymer coated on the surface of the hydrogel.
[0214] The obtained contact lenses were thoroughly washed with water, then immersed in a physiological saline solution adjusted according to ISO18369-3, and sterilized under the conditions of 121° C. and 20 minutes, and various evaluations were performed.
[0215] <Comparative Example 3>
[0216] The hydrogel prepared in Synthesis Example 1-2 was used. The hydrogel was immersed in the second polymer solution prepared in Synthesis Example 3-1 and heated at 75° C. for 2 hours in the presence of a certain amount of triethylamine in the catalyst. In this case, the hydrogel and the second polymer did not form a bond.
[0217] The obtained contact lenses were thoroughly washed with water, then immersed in a physiological saline solution adjusted according to ISO18369-3, and sterilized under the conditions of 121° C. and 20 minutes, and various evaluations were performed.
[0218] Compared with the hydrogel before coating the first polymer and the second polymer, the contact lenses of Examples 1 to 4 have no difference in transparency, water content, elongation at break, and Dk. In addition, unlike the hydrogel before coating the first polymer and the second polymer, the contact lenses of Examples 1 to 4 have good wettability and lubricity.
[0219] Furthermore, the contact lenses of Examples 1 to 4 had good durability.
[0220] That is, even when the contact lenses of Examples 1 to 4 are worn continuously for a long period of time, since the surfaces of the contact lenses have sufficient hydrophilicity and lubricity, the user can use the contact lenses for a long period of time without feeling discomfort.
[0221] In the contact lens of Comparative Example 1, only the second polymer is combined with the hydrogel, and the wettability and lubricity of the contact lens after coating treatment are good, but the durability of the coating is insufficient because the lubricity decreases after washing the contact lens 14 times and the wettability also decreases after washing the contact lens 30 times.
[0222] In the contact lens of Comparative Example 2, only the first polymer is bonded to the hydrogel, and the wettability and lubricity of the contact lens after treatment are good, but since the lubricity decreases after washing the contact lens 14 times and the wettability also decreases after washing the contact lens 30 times, the durability of the coating is insufficient.
[0223] Since the contact lens of Comparative Example 3 is not coated with the first polymer, the hydrogel and the second polymer cannot be combined, and the surface of the contact lens is not hydrophilized. Therefore, the wettability and lubricity of the contact lens after coating are poor.
[0224] [Table 1]
[0225]
[0226] [Table 2]
[0227]
[0228] [Table 3]
[0229]
[0230] [Table 4]
[0231]
[0232]
[0233] Industrial Applicability
[0234] An object of the present invention is to provide a soft contact lens whose surface has sufficient hydrophilicity and lubricity even when the soft contact lens is worn continuously for a long period of time.
[0235] Although the present invention has been described in detail and with reference to specific embodiments thereof, it will be apparent to one skilled in the art that various changes or modifications can be made to the present invention without departing from the spirit and scope of the present invention.
[0236] This application is based on the Japanese patent application filed on June 2, 2022 (Japanese Patent Application No. 2022-090437), the contents of which are incorporated herein by reference.
Claims
1. A soft contact lens comprising the following (1), (2) and (3): (1) a hydrogel (P1) having a glycidyl group and comprising a glycidyl (meth)acrylate constituent unit; (2) a first coating layer formed on the surface of the hydrogel (P1) and having carboxyl groups and / or amino groups, the first coating layer comprising a first polymer (P2) and / or a polysaccharide, the first polymer (P2) comprising a constituent unit derived from a carboxyl group-containing monomer and / or a constituent unit derived from an amino group-containing monomer, and the polysaccharide having carboxyl groups and / or amino groups; and (3) a second coating layer, which is formed on the surface of the first coating layer and has a glycidyl group, wherein the second coating layer comprises a second polymer (P3), wherein the second polymer (P3) comprises a constituent unit derived from glycidyl (meth)acrylate and a constituent unit derived from 2-(meth)acryloyloxyethyl phosphorylcholine, polyethylene glycol (meth)acrylate and / or methoxypolyethylene glycol methacrylate, wherein: The glycidyl groups of the hydrogel (P1) are bonded to the carboxyl groups and / or amino groups of the first coating layer via covalent bonds, and the carboxyl groups and / or amino groups of the first coating layer are bonded to the glycidyl groups of the second coating layer via covalent bonds.
2. The soft contact lens according to claim 1, wherein The first coating layer comprises a first polymer (P2) comprising a constituent unit derived from (meth)acrylic acid and / or a constituent unit derived from 2-aminoethyl (meth)acrylate.
3. The soft contact lens according to claim 1, wherein The second coating layer includes a second polymer (P3) comprising a constituent unit derived from 2-methacryloyloxyethyl phosphorylcholine.
4. A method for manufacturing the soft contact lens according to any one of claims 1 to 3, the method comprising the following steps: (1) immersing the hydrogel (P1) in a solution in which the first polymer (P2) and / or a polysaccharide having carboxyl groups and / or amino groups are dissolved; (2) A step of immersing the hydrogel having the first coating layer formed thereon after the immersion in step (1) in a solution in which the second polymer (P3) is dissolved.
Citation Information
Patent Citations
Information processing device and program
JP2022090437A
Surface treatment of silicone medical devices
WO2001074932A1